Conversion of 2,3-butanediol over bifunctional catalysts - Zheng, Quanxing (Kansas State University, 2016)
In this study, Cu/ZSM-5 catalysts were used to catalyze the hydrodeoxygenation of 2,3-butanediol to butenes in a single reactor in the presence of hydrogen. The carbon selectivity of butenes increased with increasing SiO₂/Al₂O₃ ratio (lowering acidity of zeolite) and H₂/2,3-butanediol ratio. Cu/ZSM-5 with a SiO₂/Al₂O₃ ratio of 280 showed the best activity toward the production of butenes. On zeolite ZSM-5(280), the carbon selectivity of butenes increased with increasing copper loading and 19.2wt% of CuO showed the highest selectivity of butenes (maximum 71%). The optimal reaction temperature is around 250 °C. Experiments demonstrated that methyl ethyl ketone (MEK) and 2-methylpropanal are the intermediates in the conversion of 2,3-butanediol to butenes. The optimal performance toward the production of butene is the result of a balance between copper and acid catalytic functions. Due to the functionalized nature of 2,3-butanediol, a variety of reactions can occur during the conversion of 2,3-butanediol, especially when multiple catalyst functionalities are present. To investigate the role of the metal (Cu) and acid sites in the process of reaction, the reaction kinetics for all major intermediate products (acetoin, MEK, 2-methylpropanal, 2-butanol and 2-methyl-1-propanol) were measured over Cu/ZSM-5(280), HZSM-5(280), and Cu/SiO₂ at 250 °C. The results showed that Cu is the active site for hydrogenation reactions, while the acidic sites on the zeolite are active for dehydration reactions. In addition, dehydration of alcohols over the zeolite is much faster than hydrogenation of ketone (MEK) and aldehyde (2-methylpropanal). A kinetic model employing Langmuir-Hinshelwood kinetics was constructed in order to predict 2,3-butanediol chemistry over Cu/ZSM-5(280). The goal of this model was to predict the trends for all species involved in the reactions. Reactions were assumed to occur on two sites (acid and metal sites) with competitive adsorption between all species on those sites. Two different types of mesoporous materials (Al-MCM-48, Al-SBA-15) and hierarchical zeolite (meso-ZSM-5) were loaded with ~20wt% CuO and investigated in the conversion of 2,3-butanediol to butenes. The results showed that the existence of mesopores on the catalysts (Al-MCM-48 and Al-SBA-15 types) could decrease the selectivities of products from cracking reactions, especially C₃= and C₅=−C₇= by comparison with the catalyst with ~20wt% CuO loaded on the regular HZSM-5(280); meanwhile, the selectivity of C₈= from oligomerization of butenes was found to increase with increasing pore size of the catalysts. With respect to Cu/meso-ZSM-5(280) catalyst, it can be seen that the catalyst performs in a similar way to both Cu/ZSM-5(280) catalyst and mesoporous copper catalysts (Cu/Al-MCM-48 and Cu/Al-SBA-15) since both micropores (diameter of ~0.55 nm) and mesopores (pore size of ~23 nm) exist on meso-ZSM-5(280). The results from Cu catalysts were compared with four other metal catalysts (Ni, Pd, Rh and Pt). It was found that Cu is not very active for hydrogenation of butenes, but is active for hydrogenation of carbonyl groups (C=O) to form hydroxyl groups (−OH). Pd, on the other hand, is active in further hydrogenating butenes and other unsaturated hydrocarbons. Both Ni and Rh catalysts are good for hydrogenation of olefins and cracking of heavy hydrocarbons; however, Rh is not as good as Ni for the hydrogenation of the carbonyl group (C=O) of MEK. In addition, Pt favors the formation of heavy aromatics such as 5-ethyl-1,2,3,4-tetrahydro-naphthalene, while Pd is active for the production of xylene.
Keywords: 2,3-butanediol; butene; hydrogenation; dehydration; mesoporous; Cu/ZSM-5